2016
DOI: 10.1007/s00204-016-1664-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic properties of XLR-11, a widely consumed synthetic cannabinoid, and of the benzoyl indole RCS-4

Abstract: Aim of this study was the investigation of the genotoxic properties of XLR-11 [1-(5-fluoropentyl)-1H-indol-3-yl](2,2,3,3-tetramethylcyclopropyl)methanone, a widely consumed synthetic cannabinoid (SC), and of the benzoyl indole RCS-4 (4-methoxyphenyl)(1-pentyl-1H-indol-3-yl)methanone). We characterized the DNA-damaging properties of these drugs in different experimental systems. No evidence for induction of gene mutations was detected in bacterial (Salmonella/microsome) tests, but clear dose-dependent effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Hyperventilation or apnea, pneumonia, alveolar infiltrates are reported in case series . Ferk et al . showed that in human lung and buccal cell lines, DNA damage occurs from SCs exposure (XRL‐11 and RCS‐4 in this study).…”
Section: Effects In Humanssupporting
confidence: 58%
See 2 more Smart Citations
“…Hyperventilation or apnea, pneumonia, alveolar infiltrates are reported in case series . Ferk et al . showed that in human lung and buccal cell lines, DNA damage occurs from SCs exposure (XRL‐11 and RCS‐4 in this study).…”
Section: Effects In Humanssupporting
confidence: 58%
“…Hyperventilation or apnea, pneumonia, alveolar infiltrates are reported in case series. 60 Ferk et al 61 showed that in human lung and buccal cell lines, DNA damage occurs from SCs exposure (XRL-11 and RCS-4 in this study). This indicates that SCs may be directly genotoxic to lung epithelium cells, independently of tobacco and/or pyrogens brought on by smoking practices.…”
Section: Undesired Effectssupporting
confidence: 57%
See 1 more Smart Citation
“…To detect DNA damage by PM 0.4–1 emission, the comet assay was carried out according to the protocols of (Tice et al, 2000; Ferk et al, 2016), with minor modifications. The BEAS-2B cells were washed extensively with 1x PBS buffer (Ca-Mg-free; pH = 7.3; 20 °C; Gibco Life Technologies, Karlsruhe, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Some adverse effects experienced by SC consumers include, but are not limited to, tachycardia, anxiety, hallucinations, suicidal thoughts, acute kidney injury and hepatotoxicity, convulsions, psychosis, and death [14,55]. Studies revealed that some SCs induced chromosomal damage in in vitro studies [56,57], suggesting a tumor risk in chronic consumers. Cannabinoid-specific therapeutic tools are not available for the clinical management of patients, which instead relies on reducing the severe symptoms of an individual [58].…”
Section: Cannabinoid Effects In Humansmentioning
confidence: 99%